Error correction techniques used by english as foreign language teachers for correcting students’ oral discourse in Intermediate I courses at the Foreign Language Department of the University of El Salvador during the semester ll, 2014. - Osegueda Gutierrez, Jonathan Armando; Ponce Acosta, Samuel Alfredo; Rosales Juarez, Aracely María; Landaverde Castillo, Manuel Alexander; Landaverde Castillo, Manuel Alexander (San Salvador, El Salvador : Universidad de El Salvador, 2015)
Learning English has become a very important tool in our society due to globalization and the growing opportunities industrialized countries offer to those who are capable of developing in a specific area. These opportunities motivate many people to learn a second language since they know they will have more chances of succeeding in their lives. However, while learning a second language, students find out it is not as easy as they thought because there are some factors that make the learning process difficult. One of the most important factors students deal with in the learning process are errors and mistakes. Errors and mistakes are a natural part of the learning process and they need to be treated as a teachable moment. Although the word “mistake” and “error” seem interchangeable, they are quite different from each other. A mistake can be thought of a slip of the tongue and can be self-corrected when attention is called. On the other hand, an error occurs because the learner does not know the correct form or structure of the language being learned, and thus it cannot be self-corrected. Even though, linguistics treats errors and mistakes differently; in this research, both will be treated the same since in daily life people see them as the same. This is how the idea of working on this project began because when the researchers were studying in the different English levels at the FLD, there were some teachers that did not correct the mistakes students made in the classes. Then when students moved to the next English level, they were making the same mistake, but in that case they were corrected by the teacher and the students tried to never make the same mistake again. Another reason for developing this research was that now that when those students began to work as teachers, they could see some colleagues making some spelling, grammar and different mistakes and they are transmitting these mistakes to their students. So, with the desire of helping English teachers and future English teachers too, the group decided to work on a research like this one with the purpose of putting together a theoretical framework for teachers and future professionals in this field that will make error correction more effective in the classroom.
Incluye anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2015
Bibliografía : hojas 70-72
Audiencia general.
Keywords: Types of error -- Causes of errors